Long-Term Effect of Surgery in Graves’ Disease: 20 Years Experience in a Single Institution - Tae-Yon Sung; Yu-mi Lee; Jong Ho Yoon; Ki-Wook Chung; Suck Joon Hong (International Journal of Endocrinology)
The present study compared the long-term outcome of subtotal thyroidectomy (ST) to that of total thyroidectomy (TT) in Graves’ disease (GD). Patients with GD requiring surgery were divided between two groups: ST and TT. Postoperative thyroid function (PoTF) changes, including hypothyroidism, euthyroidism, and hyperthyroidism, and surgical complications were analyzed 3 months and 2 years after surgery. During the study period, 350 GD patients underwent surgery, of whom 254 underwent ST and 96 underwent TT. In the ST group, the rates of hypothyroidism, euthyroidism, and hyperthyroidism were 92.5%, 6.7%, and 0.4%, respectively, after 3 months, and 86.1%, 8.6%, and 5.3%, respectively, after 2 years. No difference in the rate of surgical complication was observed between the ST and TT groups (p=0.089). Most of the ST patients showed hypothyroidism after surgery, and euthyroidism was rare. The long-term outcome of ST included noticeable PoTF changes and recurrence of GD. These results suggest that TT should be considered as a treatment option in GD requiring surgery.